PENGARUH RELATIONSHIP MARKETING DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PRODUK MUSTIKA RATU PADA GERAI DAN+DAN JAKARTA - Mona Karina; Dewi Purnama Sari (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
This study aims to determine the effect of relationship marketing and brand image on customer satisfaction for Mustika Ratu products at Dan+Dan outlets in Jakarta. The number of respondents is 100 customers who use Mustika Ratu products and have visited Dan+Dan outlets. The analysis used in this research is using SPSS 21.0 software. The analysis technique uses multiple regression analysis with least-squares equations and hypothesis testing using t-statistics and F-test to test the regression coefficients partially and simultaneously, test validity, test reliability, and test classical assumptions which include normality test, multicollinearity test, and heteroscedasticity test. . The results showed that: there was a positive and significant influence between Relationship Marketing on Customer Satisfaction; There is a positive and significant influence between Brand Image on Customer Satisfaction; Together, there is an influence between Relationship Marketing and Brand Image on Customer Satisfaction